PERBANDINGAN HASIL BELAJAR MATEMATIKA SISWA YANG DIAJAR DENGAN METODE DRILL DAN METODE EKSPOSITORI PADA KELAS VII SMP NEGERI 3 MAKASSAR - Abdul Hadi (PEDAMATH: Journal on Pedagogical Mathematics, 2019)
This research is an experimental research which aims to find out the comparison of students learning outcomes through Driil method and Expository method. Population in this research was all students at the VII grade of SMP Tut wuri HandayaniMakassar which consisted of five classes. The sample was two classes which were taken by cluster random sampling. The dara were analyzed by descriptive and inferential statistics. The result showed that: (1) the level of Handayani Makassar through Drill method had the mean score was 78,03 and categorized as high; (2) the level of students learning outcomes through expository method had the mean score was 62,15 and categorized as medium; (3) the student learning outcomes through driil method was heigher than the students learning outcomes through expository method.